Development of two Salmonella-based oral vaccines against human respiratory syncytial virus - Jalilian, F. Azizi; Yusoff, K.; Suhaimi, S.; Amini, R.; Sekawi, Z.; Jahanshiri, F. (BIOLIFE, s.a.s., 2015)
Human respiratory syncytial virus is the most common cause of bronchiolitis and other respiratory infections in infants and the elderly worldwide. We have developed two new oral vaccines using Salmonella typhi TY21a to carry and express the immunogenic epitopes of RSV fusion (F) and attachment (G) glycoproteins on its surface, separately. To evaluate the efficacy of the designed vaccines, BALB/c mice were orally immunized and then infected with RSV. Immune response analyses showed that cellmediated, mucosal and humoral immunity in the vaccinated mice were significantly enhanced compared to the control group. Both vaccines generated a balanced Th1/Th2 immune response which is crucial for efficiency of vaccines against RSV. Furthermore, histopathological examination proved that these vaccines were safe as they did not cause any Th2-associated adverse effects in the lungs of RSV-infected mice. The findings of this research suggest that Salmonella-F and Salmonella-G vaccine candidates may have strong potential to prevent RSV infection.